A micromechanical model for concrete under static loading - Liu, Yu (2014)
A micromechanical model is developed to describe the stress–strain behaviours of concrete under uniaxial compression. Two kinds of defects are considered, namely microcracks around the mortar–coarse aggregate interface or the interfacial transition zone and aligned coalesced cracks in the concrete. The mortar–coarse aggregate interfaces (interfacial transition zone) are modelled as spring layers between the mortar matrix and the inclusions (aggregates) and the existences of the microcracks in the interfacial transition zone are considered as reductions of the spring parameters under the frame of the Mori–Tanaka method. The aligned coalesced cracks in concrete (mortar + aggregate) are treated as void inclusions in the matrix of concrete using the Mori–Tanaka scheme as well. Stochastic evolution rules are adopted for both defects. The numerical examples are worked out and the proposed model is shown to be capable of estimating the moduli of concrete under its whole loading process.